A Configuration Model for Hospital Design Support Systems - Zhuoran Jia; Pirouz Nourian; Peter Luscuere; Cor Wagenaar (Buildings)
Hospital layout significantly influences hospital service quality, demanding robust tools for informed decision-making during the layout design stage. This study presents a novel Hospital Configuration Model as the foundational component of a Hospital Design Support System, which utilizes simulation modeling to provide evaluation mechanisms on hospital efficiencies and functionalities. The Hospital Configuration Model integrates four critical data types—geometric, topological, semantic, and operational—into a machine-readable digital twin, enabling comprehensive spatial and procedural analyses. The Hospital Configuration Model facilitates simulation modeling to optimize hospital layouts and predict performance metrics such as crowdingness, patient waiting times, patient walking distance, and difficulty in wayfinding. In conclusion, the Hospital Configuration Model is the core and foundation of developing the Hospital Design Support System for evaluating hospital functionalities and efficiencies, and the potential applications of the model include digital twin development, facility management, and safety enhancement. Future research directions should, in particular, include developing the proposed Hospital Design Support System and establishing a standard way of extracting hospital operational information into an industry-standard data model.